The effect of dried algae (powdered chlorella) on growth factors and body composition of rotifer Brachionus plicatilis in comparison of fresh algae (Isochrysis galbana and Nannochloropsis oculata) - Ahmad Ahmadi; Nasrollah Ahmadifard; Ebrahim Hosain Najd-Gerami (تغذیه آبزیان, 2018)
Various researches have proved that growth and biochemical content of rotifers can be affected by type and concentration of food. Microalgae as a source of food are essential for the rotifer rearing, especially for its growth, survival, protein, lipid and fatty acids contents. The present study was carried out to compare the effects of dried algae (powdered chlorella) (equivalent weight of fresh algae) on growth factor, and proximate body composition of rotifer Brachionus plicatilis in comparison with fresh algae (Isochrysis galbana and Nannochloropsis oculata) at 5×106 cells/mL. Rotifers were cultured in standard conditions in 500 mL plastic containers with initial density of 30 ind/mL. The results showed that the population growth rate of rotifers fed with I. galbana (5×106 cells/mL) was higher than the treatments fed with the chlorella powder and N. oculata (P<0.05).  High specific growth rate was in treatment fed with I. galbana (P<0.05), while the lowest was in rotifers fed with powdered chlorella. The protein and lipid contents were significantly higher in rotifers fed with chlorella powder and I. galbana, respectively. The highest DHA and DHA/EPA were significantly found in treatments fed with I. galbana, while the high amount of EPA was significantly showed in treatment fed with N. oculata. The present study showed that fresh algae can be better to create growth in marine rotifer than chlorella powder.